Burnout in medical and performance professionals working in elite football in the United Kingdom: a pilot study - Mifsud, D.; Acampora, N.; Rao, N.; Shafik, A.; Carmody, S.; Chandran, A. (Science and Medicine in Football, 2025)
Background: Despite the focus on the effect of burnout on athlete health and performance, understanding its impact on their support teams remains limited. Our primary aim was to investigate the prevalence of burnout amongst medical and performance professionals working in professional football in the UK. Methods: In this cross-sectional design study burnout risk was assessed using the Burnout Assessment Tool-23 (BAT-23). Results: A total of 162 participants completed the questionnaire. The overall average burnout score indicated a low risk of burnout; however, half (42%) of participants had individual burnout scores indicative of being at risk or very high risk of burnout. There was no statistically significant relationship between profession and burnout risk. There was also no statistically significant relationship between burnout risk and number of years working in professional football. Conclusion: This study, conducted during pre-season, suggests that medical and performance professionals working in professional football in the UK are not at risk of burnout. Measures to continue to safeguard practitioners against the effects of burnout are proposed.